Pengaruh Corporate Governance Perception Indeks (CGPI), Profitabilitas, dan Ukuran Perusahaan terhadap Nilai Perusahaan pada Bursa Efek Indonesia - Rina Marlyanti; Hasan Basri; Faisal Faisal (Jurnal Telaah dan Riset Akuntansi, 2015)
The objective of this research was to identify the partial and simultaneous effects of Corporate Governance Perception Index, profitability, and company size on the value of a company according to Indonesia Stock Exchange. Unbalanced panel data were used in this research. A number of 68 observations on Indonesia Stock Exchange (2011-2014) were found from 28 samples. Those data were then analyzed by using multiple linear regression. The process of data analysis involved the descriptive statistics for variables, simultaneous testing, and partial testing. The results indicated that Corporate Governance Perception Index, profitability, and company size simultaneously affected the value of a company according to Indonesia Stock Exchange. In addition, Corporate Governance Perception Index, profitability, and company size also partially and significantly affected the value of a company according to Indonesia Stock Exchange.KEYWORDS :  Corporate Governance Perception Index, profitability, and company size